THE HISTORICAL CONDITIONS FOR DEVELOPMENT OF THE AUTOMOTIVE INDUSTRY - Leśniak-Moczuk, Arkadiusz D. (Економічний дискурс, 2018)
Introduction. Introduction. Introduction. Introduction. Introduction. Introduction. Introduction. Introduction. Introduction. Introduction. Introduction. Development of automotive technology for military purposes has been transferred onto the civil dimension. A wooden car prototype from the second half of the 18th century in France was to serve as an artillery vehicle, and it was only at the beginning of the 19th century that steam stagecoaches in England were used for passenger transport. The rapid decrease in the demand for innovative, as for those days, technical solutions used in steam engine vehicles resulted from the growing competition of railway traffic in the form of railway, which dominated transport at that time. Only the use of an internal combustion engine for cars in 1895 in Germany sets the date of the birth of a modern car. The car industry developed in European countries, i.e. France, England, Italy, Sweden as well as in the United States of America and Japan. The history of the Polish automotive industry, in the field of construction and production of passenger cars, having its genesis at the beginning of the 20th century, shows signs of development only after the Second World War and there is no continuation in the period of the systemic transformation. Methods.Methods.Methods.Methods.Methods.Methods.Methods.Methods. The research methodology involved the use of the existing sources. Content analysis of the published source materials has been carried out as well as a comparative analysis of the data on the development of the industry in the countries, where the structural thought contributed to the emergence of the automotive industry. Results. Results.Results.Results. Results.Results. It was not until the industrial era that universal access to the possession and use of a car for civil purposes, a car produced serially in standard technical and aesthetic parameters, became available.Discussion. Discussion. Discussion. Discussion. Discussion. Discussion. Discussion. Discussion. Discussion. The two-hundred-year evolution of the energy resources used to power cars takes its origins from the tractive force of animals, through such mechanical solutions as those using wind power (sail), springs, human muscles (pedals), water vapor (steam engine), gasoline (gasoline engine) to the experiments with biofuels and electricity. The search for new solutions was a response to the demand to increase the speed of movement in physical space.